Pengaruh Projek Penguatan Profil Pelajar Pancasila Terhadap Karakter Profil Pelajar Pancasila Siswa SMA Negeri 1 Medan - Palma Juanta; Veronika Andriani Br Manalu; Faeri Grace Damai Yanti Halawa (CV. ITTC INDONESIA, 2024)
This study aims to determine the influence of the implementation of the P5 (Profil Pelajar Pancasila) strengthening project on student character at SMA Negeri 1 Medan. The research method used is quantitative with correlation analysis techniques, coefficient of determination, and T-test. The research sample is 100 students who were selected randomly. The results of the study showed that there was a significant positive influence between the implementation of the P5 strengthening project and the character of students at SMA Negeri 1 Medan. The coefficient of determination of 0.223 indicates that 22.3% of the variation in student character is influenced by the P5 strengthening project.The findings of this study show that the P5 strengthening project is one of the effective strategies for developing student character at SMA Negeri 1 Medan.